Challenges of Democracy in Bosnia and Herzegovina Thirty Years After Dayton - Selma Ćosić; Elma Huruz Memović (Društvene i Humanističke Studije, 2025)
Thirty years after the signing of the Dayton Peace Agreement, Bosnia and Herzegovina (BiH) faces numerous challenges in building a stable, functional political system and a coherent society. The Dayton Agreement, which ended the war in 1995, established a complex political structure based on ethnic principles, which created the basic framework for peace, but also for the political difficulties that have accompanied BiH over the past thirty years. Some authors believe that in our political system there are certain mechanisms of consociational democracy that are usually applied in divided, post-conflict societies in order to ensure security stability and, over time, the ultimate goal of liberal democracy. It is evident that none of these mechanisms has managed to produce completely positive outcomes in terms of respect for democratic standards and norms as well as a functional political system based on consensus on issues of national importance. The question that the authors leave open in the end is what is the alternative and what is the way to establish more functional solutions on the way to a more stable, democratic government and social cohesion for BiH?